Kinematics and Workspace of a Reconfigurable Robotic Leg Based on the Peaucellier-Lipkin Mechanism - Núñez-Altamirano, Diego (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This work describe the kinematics and workspace of a Reconfigurable Robotic Leg based on the Peaucellier-Lipkin mechanism that is modified for use in walking machines. It has the ability to describe straight line or curved paths depending on the selected ratio between the lengths of two of its links. It means that the one degree-of-freedom mechanism was transformed into a more sophisticated parallel kinematic chain by the inclusion of four more degrees of freedom. This leg has five DOFs, but only two of them are used for the support and transfer phases. The other three DOFs are used exclusively when the foot needs a reconfiguration to describe a different path during the transfer phase.